The holiday makers : [U+01C2]b understanding the impact of leisure and travel - Krippendorf, Jost.; ScienceDirect eBooks (Oxford ; Boston : Butterworth-Heinemann, 1999)
The Holiday Makers is thought-provoking and profound in its analysis of the present and future patterns of work and leisure. The author analyses the different forms of tourism, examines the effects on the indigenous countries and their people, and outlines positive steps to reconcile people's holiday requirements with the world's economic and social structures. International best-seller Thought-provoking and profound in its analysis of the present and future patterns of work and leisure.
Introduction; The model of life in industrial society work, home, free time, travel; The holiday machine or: the recreation cycle; For a humanization of everyday life; Proposals for the humanization of travel; References; Index.
Includes bibliographical references and index.
Print version record.
Safari Books Online
Elsevier
Keywords: Tourism; Recreation; Recreation; Tourism; Electronic books